Cannabidiol for Pain Treatment: Focus on Pharmacology and Mechanism of Action - Mlost, Jakub (Int J Mol Sci, 2020)
Cannabis has a long history of medical use. Although there are many cannabinoids present in cannabis, Δ9tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) are the two components found in the highest concentrations. CBD itself does not produce typical behavioral cannabimimetic effects and was thought not to be responsible for psychotropic effects of cannabis. Numerous anecdotal findings testify to the therapeutic effects of CBD, which in some cases were further supported by research findings. However, data regarding CBD’s mechanism of action and therapeutic potential are abundant and omnifarious. Therefore, we review the basic research regarding molecular mechanism of CBD’s action with particular focus on its analgesic potential. Moreover, this article describes the detailed analgesic and anti-inflammatory effects of CBD in various models, including neuropathic pain, inflammatory pain, osteoarthritis and others. The dose and route of the administration-dependent effect of CBD, on the reduction in pain, hyperalgesia or allodynia, as well as the production of pro and anti-inflammatory cytokines, were described depending on the disease model. The clinical applications of CBD-containing drugs are also mentioned. The data presented herein unravel what is known about CBD’s pharmacodynamics and analgesic effects to provide the reader with current state-of-art knowledge regarding CBD’s action and future perspectives for research.